Queering YouTube gaming a single case study of OhMyV33nus and the performance queerness in video game live streaming and vlogging on YouTube - Yumol, David Paolo Nicolas; Brillon, Cherish Aileen A. (Quezon City University of the Philippines, Diliman, 2025)
Queer identities continue to be marginalized in online video gaming spaces due in part to their lack of visibility in online gaming communities and representation in video games. The rise of OhMyV33nus, a popular queer professional esports player and video game content creator, and her performance of her gender through her video game content could shed light on how queer people queer online gaming spaces and their play. The study explores the connection between online self-presentation, particularly the performance of gender, and the affordances of video games and social media platforms. Specifically, it examines how queerness is performed and negotiated in the case of OhMyV33nus’s YouTube channel. The study employs a methodology of single case study and multimodal textual analysis guided by the concepts of Online Self-Presentation (Goffman, 1956), Gender Performativity (Butler, 1999), and Affordances (Gibson, 1979). Findings show that OhMyV33nus utilizes various strategies and the different dimensions of her YouTube content to perform and negotiate her queerness. The study reflected how gender performance could be observed on YouTube in varying degrees based on the genre of the game, genre of the video, and the type of media content.
Thesis
Includes bibliography
Keywords: Gays in popular culture -- Philippines; Sexual minorities -- Philippines; Sexual minorities in mass media -- Philippines; Video gamers -- Social aspects -- Philippines; Video blogs -- Philippines